Quaternary ammonium salt modified polyurethane ice-repellent coating and method for preparing the same
Patent Information
- Application Number
- CN202610908200.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-09-04
AI Technical Summary
[0004]本发明的目的在于克服上述技术不足,提出一种季铵盐改性聚氨酯防冰涂层及其制备方法,旨在解决现有的防冰涂层耐久性与防冰效能平衡的问题
(1)适配性强,结构可控:可通过精准调控NCO与OH的摩尔比,分别制备OH封端和NCO封端两种聚氨酯,能根据不同应用场景需求灵活选择改性体系。
Smart Images

Figure CN122686233A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, and in particular to a quaternary ammonium salt modified polyurethane anti-icing coating and its preparation method. Background Technology
[0002] In cold environments, ice and snow accumulation is widespread in various engineering fields such as transportation, energy equipment, and infrastructure. Moisture in the air condenses and freezes on material surfaces, not only altering their physical properties but also posing a serious threat to equipment operation and structural safety, leading to a series of safety accidents and huge economic losses. Therefore, the development of efficient and reliable anti-icing / de-icing technologies is of paramount necessity and urgency. In power systems, ice can cause a surge in transmission line loads, line galloping, and even line breaks, severely affecting the stability and security of power transmission. In wind power and aviation, ice alters the aerodynamic performance of equipment, causing significant power losses and long-term energy degradation. Icing on wind turbine blades in cold regions can result in a 10% to 30% loss in power generation, severely restricting the development of the wind power industry. Icing on aircraft wings and engine air intakes can even lead to catastrophic accidents with fatalities. In transportation, highway bridge surfaces and cables are prone to icing at low temperatures. Slippery roads cause vehicles to skid and lose control, significantly increasing braking distance and easily leading to traffic accidents, resulting in casualties and property damage. These icing problems have long plagued related industries. Currently, existing anti-icing technologies are mainly divided into two categories: active anti-icing and passive anti-icing. Active anti-icing technologies, such as electrothermal, hot air, and mechanical vibration, can effectively remove ice buildup and are widely used in aero engines and wind turbine blades. However, these methods generally face engineering bottlenecks such as high energy consumption, complex system structure, and high maintenance costs, making it difficult to achieve long-term large-scale application. In contrast, passive anti-icing technologies that do not require external energy input have attracted much attention and become a research hotspot in the field of anti-icing.
[0003] In recent years, emerging passive anti-icing technologies such as superhydrophobic surfaces, superhydrophilic surfaces, and liquid lubricating infused surfaces (SLIPS) have been continuously developing. These technologies effectively reduce water droplet wetting time, inhibit ice nucleation, delay freezing time, and reduce ice adhesion strength by controlling the chemical composition of the material surface or constructing multi-scale micro / nano structures. However, under complex working conditions such as extreme high pressure, high humidity, and mechanical wear, these passive anti-icing materials still face problems such as insufficient durability and difficulties in large-scale preparation, failing to meet the needs of practical engineering applications. Summary of the Invention
[0004] The purpose of this invention is to overcome the above-mentioned technical deficiencies and propose a quaternary ammonium salt modified polyurethane anti-icing coating and its preparation method, aiming to solve the problem of balancing the durability and anti-icing performance of existing anti-icing coatings.
[0005] To achieve the above-mentioned technical objectives, a first aspect of the present invention provides a method for preparing a quaternary ammonium salt modified polyurethane anti-icing coating, the method comprising the following steps: S1, mixing a polyol, a polyisocyanate, and a first organic solvent, and performing a first heating reflux reaction in the absence of air to obtain isocyanate-terminated PrePU; S2, mixing the isocyanate-terminated PrePU, a chain extender, and a second organic solvent, controlling the isocyanate index R to 0.6~0.9 or 1.1~ 1.5. Under air-isolated conditions, a second heating reflux reaction is carried out, followed by cooling to obtain PU-OH or PU-NCO; S3. A quaternary ammonium salt solution is added to the PU-OH or PU-NCO, and the reaction is carried out to obtain a solution containing PU-OH-QAS or a solution containing PU-NCO-QAS, wherein the quaternary ammonium salt solution includes 2,3-epoxypropyltrimethylammonium chloride and a third organic solvent; S4. The solution containing PU-OH-QAS or the solution containing PU-NCO-QAS is coated onto the surface of the substrate and cured to obtain a quaternary ammonium salt modified polyurethane anti-icing coating.
[0006] In some embodiments, the polyol includes one or more of polycaprolactone diol, polyether diol, and polycarbonate diol; the polyisocyanate includes diisocyanate, which includes one or more of diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate; the first organic solvent includes one or more of ethyl acetate, butyl acetate, and cyclohexanone; the isocyanate index R of the polyol and the polyisocyanate is 1.2 to 1.5; in the mixture of the polyol, the polyisocyanate, and the first organic solvent, the total mass percentage of the polyol and the polyisocyanate is 30% to 70%; the first reflux reaction is carried out under stirring at a speed of 200 r / min to 400 r / min; the temperature of the first reflux reaction is 80°C to 100°C; and the time of the first reflux reaction is 6 h to 8 h.
[0007] In some embodiments, the polyol comprises polycaprolactone diol, wherein the number average molecular weight of the polycaprolactone diol is 500 to 10,000; and / or, the polyisocyanate comprises diisocyanate, wherein the diisocyanate comprises one or more of diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
[0008] In some embodiments, the chain extender includes 2,2-dimethylolpropionic acid; the second organic solvent includes cyclohexanone; in the mixture of the isocyanate-terminated PrePU, the chain extender, and the second organic solvent, the sum of the mass percentages of the isocyanate-terminated PrePU and the chain extender is 15% to 30%.
[0009] In some embodiments, the second heating reflux reaction is carried out under stirring at a speed of 200 r / min to 400 r / min; the temperature of the second heating reflux reaction is 80°C to 100°C; and the time of the second heating reflux reaction is 6 h to 8 h.
[0010] In some embodiments, in step S3, the 2,3-epoxypropyltrimethylammonium chloride in the quaternary ammonium salt solution has a mass percentage of 5% to 20%; the third organic solvent includes chloroform; and the amount of 2,3-epoxypropyltrimethylammonium chloride is equal to the amount of the chain extender.
[0011] In some embodiments, in step S3, the quaternary ammonium salt solution is added at a rate of 0.5 mL / min to 2 mL / min; the reaction temperature is 40°C to 60°C; the reaction time is 6 h to 8 h; and the reaction is carried out under stirring.
[0012] In some embodiments, the areal density of PU-OH-QAS or PU-NCO-QAS on the substrate is 0.01 g / cm³. 2 ~0.05 g / cm 2 .
[0013] In some embodiments, the substrate includes a metal sheet, which includes one or more of iron sheets, steel sheets, aluminum sheets, and copper sheets.
[0014] In a second aspect, the present invention provides a quaternary ammonium salt modified polyurethane anti-icing coating, wherein the anti-icing coating is prepared by the preparation method of the quaternary ammonium salt modified polyurethane anti-icing coating described in the first aspect of the present invention.
[0015] Compared with the prior art, the beneficial effects of the present invention include: In the preparation method of the quaternary ammonium salt modified polyurethane anti-icing coating proposed in this invention, hydrophilic sites are provided by a chain extender such as 2,2-dimethylolpropionic acid, to prepare two types of polyurethane with -OH and -NCO end caps, respectively. The strong hydrophilicity of the quaternary ammonium salt grafting is beneficial for the rapid formation of a stable water film, delaying freezing and overcoming the shortcomings of insufficient hydrophilicity in conventional coatings. Furthermore, the hydrophilic mechanism of the quaternary ammonium salt modified polyurethane anti-icing coating of this invention is more stable. The quaternary ammonium salt is fixed to the side chain of the polyurethane molecule through covalent grafting, without relying on internal ion migration. This results in strong resistance to contamination, erosion, and freeze-thaw cycles, and a long-lasting anti-icing effect, effectively extending the coating's service life. In summary, the quaternary ammonium salt modified polyurethane anti-icing coating proposed in this invention possesses both stable anti-icing performance and durability. Attached Figure Description
[0016] Figure 1 This is a schematic flowchart of the preparation method of the quaternary ammonium salt modified polyurethane anti-icing coating proposed in the embodiments of the present invention; Figure 2 These are the infrared spectra of PU-NCO and PU-NCO-QAS prepared in Example 4 of this invention; Figure 3 This is the infrared spectrum of PU-OH-QAS prepared in Example 1 of this invention; Figure 4 This is a schematic diagram of the surface water contact angle of the anti-icing coating prepared in Example 1 of the present invention. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0018] In a first aspect, this invention provides a method for preparing a quaternary ammonium salt modified polyurethane anti-icing coating. Please refer to [link to relevant documentation]. Figure 1 The method includes the following steps: S1. A polyol, a polyisocyanate, and a first organic solvent are mixed and subjected to a first heating reflux reaction in the absence of air to obtain isocyanate-terminated PrePU.
[0019] In some embodiments, the polyol includes one or more of polycaprolactone diol, polyether diols (such as PPG-2000, where PPG is an abbreviation for polypropylene glycol and 2000 is the number-average molecular weight), and polycarbonate diols (such as PCDL-2000, where PCDL is an abbreviation for polycarbonate diol and 2000 is the number-average molecular weight). The reaction of these polyols with polyisocyanates can subsequently generate polyurethane (PU). Furthermore, these polyols can control the soft segment properties of the polyurethane molecular chain, as well as the flexibility and hydrolysis resistance of the product after subsequent grafting of quaternary ammonium salts.
[0020] In other embodiments, the polyol comprises polycaprolactone diol (PCL) having a number-average molecular weight of 500 to 10,000. As an example, the number-average molecular weight Mn of the PCL can be 500, 1,000, 3,000, 5,000, 7,000, 9,000, 10,000, or any combination of two of these values, thereby improving the flexibility and hydrolysis resistance of the final anti-icing coating.
[0021] In some embodiments, the polyisocyanate includes diisocyanates (such as MDI-50, a mixture of 2,4-diphenylmethane diisocyanate and 4,4'-diphenylmethane diisocyanate), specifically, the diisocyanate includes one or more of diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI). The aforementioned polyisocyanates can improve the yellowing resistance of modified polyurethane coatings without affecting the overall reaction structure, making them suitable for long-term outdoor use.
[0022] In some embodiments, the first organic solvent comprises butyl acetate. This further facilitates the reaction.
[0023] In some embodiments, the isocyanate index R of the polyol and the polyisocyanate is 1.2 to 1.5. As an example, R can be 1.2, 1.3, 1.4, 1.5, or any combination of two of these values. The isocyanate index is a key formulation parameter in polyurethane synthesis, representing the equivalent ratio of isocyanate groups (NCO) to hydroxyl groups (OH). The theoretical value is 1:1, or 1. Within the above range, this index can regulate the chemical reaction balance, resulting in better mechanical properties, thermal stability, microstructure, and aging resistance of the polyurethane material, and is also beneficial for subsequent chain extension and grafting reactions.
[0024] In some embodiments, in the mixture of the polyol, the polyisocyanate, and the first organic solvent, the sum of the mass percentages of the polyol and the polyisocyanate is 30% to 70%. For example, it can be 30%, 40%, 50%, 60%, 70%, or any combination of two of these values, thereby further facilitating the reaction.
[0025] In some embodiments, the first heating reflux reaction is carried out under stirring at a speed of 200 r / min to 400 r / min. As an example, the stirring speed can be 200 r / min, 300 r / min, 400 r / min, or any combination of two of the above values, which is beneficial for forming a uniform and stable PrePU (polyurethane prepolymer).
[0026] In some embodiments, the temperature of the first heating reflux reaction is 80°C to 100°C. As an example, the temperature of the first heating reflux reaction can be 80°C, 85°C, 90°C, 95°C, 100°C, or any two of the above values, which further facilitates the reaction.
[0027] In some embodiments, the duration of the first heating reflux reaction is 6 h to 8 h. As an example, it can be 6 h, 6.5 h, 7 h, 7.5 h, 8 h, or any range of two of the above values, thereby facilitating the full progress of the reaction.
[0028] As an example, step S1 is performed as follows: A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. The apparatus was checked for leaks to ensure there were no gas or liquid leaks. Polyols (e.g., polycaprolactone diol-2000 (PCL-2000)) and polyisocyanates (e.g., MDI-50, 99% purity) were added to the four-necked flask, with the isocyanate index R controlled to 1.2–1.5. PCL-2000 and MDI-50 were added sequentially, followed by an appropriate amount of butyl acetate as a solvent, adjusting the system concentration to 30%–70%. The stirrer was turned on, and the stirring speed was controlled at 200–400 r / min. The temperature was slowly increased to 80–100°C and maintained at this temperature for 6–8 hours, during which the system status was observed regularly to ensure uniform reaction. After the reaction, isocyanate (NCO)-terminated PrePU was obtained. It was cooled to room temperature, sealed, and stored for subsequent chain extension reactions.
[0029] S2. The isocyanate-terminated PrePU, chain extender and second organic solvent are mixed, and the isocyanate index R is controlled to 0.6 ~ 0.9 or 1.1 ~ 1.5. Under the isolation of air, a second heating reflux reaction is carried out and cooled to obtain PU-OH or PU-NCO.
[0030] It is understood that in step S2, when the isocyanate index R is 0.6 to 0.9, the product obtained by the reaction is PU-OH, and when the cyanate index R is 1.1 to 1.5, the product obtained by the reaction is PU-NCO.
[0031] In some embodiments, the chain extender comprises 2,2-dimethylolpropionic acid (DMPA). Thus, the chain extender can introduce -COOH groups onto the polyurethane backbone.
[0032] In some embodiments, the second organic solvent comprises cyclohexanone. This further facilitates the introduction of -COOH onto the polyurethane backbone.
[0033] In some embodiments, in the mixture of isocyanate-terminated PrePU, chain extender, and second organic solvent, the combined mass percentage of the isocyanate-terminated PrePU and the chain extender is 15% to 30%. For example, it could be 15%, 18%, 20%, 23%, 25%, 27%, 30%, or any combination of two of these values, thereby further facilitating the formation of PU-OH or PU-NCO.
[0034] In some embodiments, the isocyanate index R in step S2 is 1.1 to 1.5. As an example, R can be 1.1, 1.2, 1.3, 1.4, 1.5, or any combination of two of these values. An index within this range is advantageous for capping the polyurethane main chain with NCO groups, generating PU-NCO. In other embodiments, the isocyanate index R in step S2 is 0.6 to 0.9. As an example, R can be 0.6, 0.7, 0.8, 0.9, or any combination of two of these values. An index within this range is advantageous for capping the polyurethane main chain with OH groups, generating PU-OH.
[0035] In some embodiments, the second heating reflux reaction is carried out under stirring at a speed of 200 r / min to 400 r / min. As an example, the stirring speed can be 200 r / min, 300 r / min, 400 r / min, or any combination of two of the above values, which is beneficial for forming a homogeneous and stable PU-OH or PU-NCO.
[0036] In some embodiments, the temperature of the second heating reflux reaction is 80°C to 100°C. As an example, the temperature of the second heating reflux reaction can be 80°C, 85°C, 90°C, 95°C, 100°C, or any combination of two of the above values, thereby further facilitating the reaction.
[0037] In some embodiments, the second heating reflux reaction time is 6 h to 8 h. As an example, it can be 6 h, 6.5 h, 7 h, 7.5 h, 8 h, or any range of two of the above values, thereby facilitating the full progress of the reaction.
[0038] As an example, step S2 is performed as follows: Take the PrePU prepared in step S1 above and transfer it to a new four-necked flask. Construct the same reaction apparatus as for the PrePU synthesis. Add 98% pure DMPA as a chain extender to the flask, using cyclohexanone as a solvent, and adjust the system concentration to 15-30%, controlling the isocyanate index R to 0.6-0.9. Start stirring and slowly heat to 80-100℃, maintaining this temperature for 6-8 hours, while controlling the stirring speed at 200-400 r / min. During the reaction, the content of NCO groups in the system can be detected by sampling. When the NCO group content is zero, the reaction has reached its endpoint. Stop heating, allow it to cool naturally to room temperature, and obtain PU-OH. Seal and store for later use.
[0039] or, Using the same reaction apparatus as the PU-OH synthesis, the same batch of PrePU prepared in step S1 was added to a four-necked flask, and cyclohexanone was added as a solvent to adjust the system concentration to 15-30%. 98% pure DMPA (2,2-dimethylolpropionic acid) was added as a chain extender, and the isocyanate index ηR was controlled to 1.1-1.5 to ensure an excess of NCO groups. The temperature was slowly raised to 80-100℃ and maintained at this temperature for 6-8 hours, with a stirring speed of 200-400 r / min. Samples were taken periodically during the reaction, and the residual amount of NCO groups in the system was detected by chemical titration until the residual amount reached a stable value, which was considered the reaction endpoint. After the reaction, the mixture was cooled to room temperature to obtain the PU-NCO product, which was sealed and stored for subsequent quaternary ammonium salt grafting reactions.
[0040] S3. Add the quaternary ammonium salt solution to the PU-OH or the PU-NCO, and react to obtain a solution containing PU-OH-QAS or a solution containing PU-NCO-QAS, wherein the quaternary ammonium salt solution includes 2,3-epoxypropyltrimethylammonium chloride and a third organic solvent.
[0041] In this step, 2,3-epoxypropyltrimethylammonium chloride is selected as a quaternary ammonium salt with epoxy active groups. Compared with other quaternary ammonium salts such as alkyl quaternary ammonium salts, it can be covalently grafted with polyurethane segments through epoxy groups, avoiding the migration and precipitation of quaternary ammonium salts, giving the coating stable hydrophilicity and long-lasting antibacterial properties. Moreover, the reaction conditions are mild and there are few side reactions, making it more suitable for anti-icing coating systems.
[0042] In some embodiments, the 2,3-epoxypropyltrimethylammonium chloride in the quaternary ammonium salt solution comprises 5% to 20% by mass. For example, it can be 5%, 10%, 15%, 20%, or any two of the above values. This facilitates the grafting reaction between the quaternary ammonium salt and the polyurethane segments, further enhancing the hydrophilicity of the anti-icing coating and improving the anti-icing effect.
[0043] In some embodiments, the addition rate of the quaternary ammonium salt solution is 0.5 mL / min to 2 mL / min. For example, it can be 0.5 mL / min, 0.8 mL / min, 1 mL / min, 1.2 mL / min, 1.5 mL / min, 1.7 mL / min, 2 mL / min, or any combination of two of the above values. This avoids excessively rapid dropping rates that could lead to violent local reactions, a sudden increase in system viscosity, or even gelation, which would affect the uniformity of the grafting reaction and the properties of the product.
[0044] In some embodiments, the third organic solvent comprises chloroform. This further facilitates the formation of PU-OH-QAS or PU-NCO-QAS.
[0045] In some embodiments, the amount of 2,3-epoxypropyltrimethylammonium chloride is equal to the amount of the chain extender. This facilitates the complete formation of PU-OH-QAS or PU-NCO-QAS.
[0046] In some embodiments, the reaction temperature is 40°C to 60°C. For example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, or any combination of two of the above values. This allows for a more complete reaction, stable product properties, and reduces side reactions and molecular structure damage caused by excessively high temperatures.
[0047] In some embodiments, the reaction time is 6 h to 8 h. As an example, it can be 6 h, 6.5 h, 7 h, 7.5 h, 8 h, or any range of two of the above values, thereby allowing sufficient reaction to generate PU-OH-QAS or PU-NCO-QAS.
[0048] In some embodiments, the reaction is carried out under stirring. This facilitates the formation of a homogeneous and stable product.
[0049] As an example, in this embodiment of the invention, the structural formulas of PU-OH-QAS(a) and PU-NCO-QAS(b) are as follows:
[0050] a
[0051] b The structure of -A- is as follows:
[0052] In the above structural formula, a = 4 ~ 18, M = 1 ~ 10, and N = 1 ~ 10.
[0053] As an example, step S3 is performed as follows: Take the PU-OH prepared in step S2 and add it to a four-necked flask. Start stirring to disperse it evenly. Separately, take 2,3-epoxypropyltrimethylammonium chloride in an equimolar ratio of DMPA and prepare a quaternary ammonium salt solution with a mass fraction of 5% to 20% using chloroform as a solvent. Stir until completely dissolved and without obvious precipitation. Slowly add the prepared quaternary ammonium salt solution dropwise to the PU-OH system at a rate of 0.5 mL / min to 2 mL / min, keeping the stirring constant during the addition. After the addition is complete, adjust the reaction temperature to 40 to 60℃ and maintain the temperature for 6 to 8 hours. Observe the viscosity change of the system during the reaction to ensure that the grafting reaction proceeds fully. After the reaction is complete, PU-OH-QAS is obtained. After cooling to room temperature, seal and store for later use.
[0054] or, Take the PU-NCO prepared in step S2 and add it to a four-necked flask. Start stirring to form a homogeneous system. Following the above method, prepare a 5%–20% (w / w) quaternary ammonium salt solution, stir until completely dissolved, and then add it dropwise to the PU-NCO system at a rate of 0.5 mL / min–2 mL / min. Control the dropping rate during the addition process to avoid excessively vigorous local reactions. After the addition is complete, adjust the reaction temperature to 40–60℃ and maintain the temperature for 6–8 hours. Observe the system state regularly during this period to ensure sufficient grafting of the quaternary ammonium salt and polyurethane molecules. After the reaction is complete, cool to room temperature to obtain PU-NCO-QAS, which should be sealed and stored for later use.
[0055] S4. Apply a solution containing PU-OH-QAS or a solution containing PU-NCO-QAS to the surface of the substrate and cure it to obtain a quaternary ammonium salt modified polyurethane anti-icing coating.
[0056] In some embodiments, the areal density of PU-OH-QAS or PU-NCO-QAS on the substrate is 0.01 g / cm³. 2 ~0.05 g / cm 2 For example, it could be 0.01 g / cm³. 2 0.02 g / cm 2 0.03 g / cm 2 0.04 g / cm 2 0.05 g / cm 2 Or it can be a range of any two of the above values, which makes it easier for the subsequent coating to have good anti-icing performance and to avoid excessively high surface density.
[0057] In some embodiments, the substrate includes a metal sheet, which includes one or more of iron sheets, steel sheets, aluminum sheets, and copper sheets.
[0058] As an example, step S4 is performed as follows: The solution containing PU-OH-QAS or the solution containing PU-NCO-QAS from step S3 is added at a concentration of 0.01 g / cm³. 2 ~0.05 g / cm 2 The areal density is coated onto the surface of metal sheets such as iron sheets, steel sheets, aluminum sheets, and copper sheets and cured at room temperature for 8 hours.
[0059] As an example, the preparation method of this invention involves the following chemical reaction equations during the preparation of the quaternary ammonium salt modified polyurethane anti-icing coating:
[0060] The structural formula for -A- is as follows:
[0061] The structural formula for -R- is as follows:
[0062] In the above structural formula, a = 4~18, b = 4~18, and m = 1~10.
[0063] In summary, the preparation method of the quaternary ammonium salt modified polyurethane anti-icing coating of the present invention has the following advantages: (1) Strong adaptability and controllable structure: By precisely controlling the molar ratio of NCO to OH, two types of polyurethanes, OH-terminated and NCO-terminated, can be prepared respectively, and the modification system can be flexibly selected according to the needs of different application scenarios.
[0064] (2) Stable and reliable hydrophilicity: The quaternary ammonium salt is fixed to the side chain of the polyurethane molecule by covalent grafting, which makes the hydrophilicity less prone to decay and less susceptible to contamination. Compared with the ion migration hydrophilic method in the target literature, it has better stability and faster start-up.
[0065] (3) Easy to scale up production: The process is mild and simple, the reaction conditions are easy to control, and the raw materials used are all conventional chemical raw materials. No special equipment or complex processes are required. It can be directly adapted to existing industrial production lines, reducing mass production costs.
[0066] (4) Outstanding environmental performance: No fluorine-containing raw materials are used throughout the process. The raw materials are non-toxic and easy to recycle. There is no harmful pollution in the production process, which meets the requirements of green industrialization and is not restricted by environmental protection policies.
[0067] (5) Significantly improved hydrophilicity and anti-icing efficiency: DMPA provides hydrophilic sites, and quaternary ammonium salt grafting provides strong hydrophilicity, rapidly forming a stable water film and delaying freezing, thus overcoming the shortcomings of insufficient hydrophilicity in conventional coatings. The hydrophilic mechanism is more stable, with covalent bonds fixing hydrophilic groups, eliminating reliance on internal ion migration. It exhibits strong resistance to contamination, erosion, and freeze-thaw cycles, providing long-lasting anti-icing effects and effectively extending the coating's service life. It has great industrialization potential, with significant technological differentiation. It possesses stable anti-icing performance while also considering process simplicity and environmental friendliness, making it suitable for various engineering applications. No additional production equipment is required, resulting in low industrialization difficulty and broad prospects.
[0068] In a second aspect, the present invention provides an anti-icing coating, which is prepared using the anti-icing coating preparation method described in the first aspect of the present invention. Therefore, the anti-icing coating proposed by the present invention possesses all the beneficial effects of the above-described methods, which will not be elaborated further here.
[0069] It is understood that in the embodiments of the present invention, purity refers to the mass percentage.
[0070] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0071] Example 1 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0072] Transfer all of the PrePU to a new four-necked flask, add 1.52 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.9. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0073] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0074] Take 10g of PU-OH-QAS and apply it to an iron sheet (a 100*60*0.3mm test-grade tinplate sheet; the same iron sheet and coating amount were used in other examples and comparative examples). After curing for 8 hours, measure its hydrophilicity and anti-icing properties.
[0075] Example 2 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0076] Transfer all of the PrePU to a new four-necked flask, add 2.28 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.6. Start stirring, heat to 90℃, and react at this temperature for 7 h. Sample and test for NCO residue until stable. Cool to room temperature to obtain PU-OH, and seal for later use. Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0077] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0078] Example 3 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0079] Transfer all of the PrePU to a new four-necked flask, add 3.42 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.4. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0080] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0081] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0082] Example 4 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0083] Using the same reaction apparatus, all of the PrePU was added to a four-necked flask, and cyclohexanone was added as a solvent to adjust the system concentration to 25%. 1.05 g of 98% pure DMPA was added as a chain extender, and the isocyanate index R was controlled to 1.3. Stirring was started, the temperature was raised to 90°C, and the reaction was maintained at this temperature for 7 hours. Samples were taken periodically during the reaction, and the residual amount of NCO groups in the system was determined by chemical titration until stable. The mixture was then cooled to room temperature to obtain PU-NCO, which was sealed for later use.
[0084] Add 10.0 g of PU-NCO to a four-necked flask and stir to form a homogeneous system. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform, stir until completely dissolved, and then slowly add it dropwise to the PU-NCO system. After the addition is complete, adjust the reaction temperature to 60℃ and stir the reaction at this temperature for 6 h. Cool to room temperature to obtain PU-NCO-QAS, and store in a sealed container.
[0085] 10 g of PU-NCO-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0086] Example 5 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0087] Using the same reaction apparatus, all of the above PrePU was added to a four-necked flask, and cyclohexanone was added as a solvent to adjust the system concentration to 25%. 1.24 g of 98% pure DMPA was added as a chain extender to control the isocyanate index R to 1.1. Stirring was started, the temperature was raised to 90℃, and the reaction was maintained at this temperature for 7 h. Samples were taken periodically during the reaction, and the residual amount of NCO groups in the system was determined by chemical titration until stable. The mixture was then cooled to room temperature to obtain PU-NCO, which was sealed for later use.
[0088] Add 10.0 g of PU-NCO to a four-necked flask and stir to form a homogeneous system. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform, stir until completely dissolved, and then slowly add it dropwise to the PU-NCO system. After the addition is complete, adjust the reaction temperature to 60℃ and stir the reaction at this temperature for 6 h. Cool to room temperature to obtain PU-NCO-QAS, and store in a sealed container.
[0089] 10 g of PU-NCO-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0090] Example 6 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0091] Using the same reaction apparatus, all of the PrePU was added to a four-necked flask, and cyclohexanone was added as a solvent to adjust the system concentration to 25%. 0.91 g of 98% pure DMPA was added as a chain extender to control the isocyanate index R to 1.5. Stirring was started, and the temperature was raised to 90°C and maintained for 7 hours. Samples were taken periodically during this time, and the residual NCO groups in the system were determined by chemical titration until stable. The mixture was then cooled to room temperature to obtain PU-NCO, which was sealed for later use.
[0092] Add 10.0 g of PU-NCO to a four-necked flask and stir to form a homogeneous system. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform, stir until completely dissolved, and then slowly add it dropwise to the PU-NCO system. After the addition is complete, adjust the reaction temperature to 60℃ and stir the reaction at this temperature for 6 h. Cool to room temperature to obtain PU-NCO-QAS, and store in a sealed container.
[0093] 10 g of PU-NCO-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0094] Example 7 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 8.2 g of IPDI were added, and butyl acetate was added to adjust the system concentration to 50%. Stirring was started (250 r / min), and the temperature was slowly increased to 90℃. The reaction was maintained at this temperature for 7 h to obtain PrePU, which was then cooled to room temperature and sealed for later use.
[0095] Transfer all of the PrePU to a new four-necked flask, add 1.52 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.9. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0096] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0097] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0098] Example 8 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 6.7 g of HDI were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90℃. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0099] Transfer all of the PrePU to a new four-necked flask, add 1.52 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.9. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0100] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0101] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0102] Example 9 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 10.6 g of PCL-530 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0103] Transfer all of the PrePU to a new four-necked flask, add 1.52 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.9. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0104] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0105] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0106] Example 10 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 200 g of PCL-10000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0107] Transfer all of the PrePU to a new four-necked flask, add 1.52 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.9. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0108] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0109] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0110] Example 11 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PPG-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0111] Transfer all of the PrePU to a new four-necked flask, add 1.52 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.9. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0112] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0113] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0114] Example 12 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCDL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use.
[0115] Transfer all of the PrePU to a new four-necked flask, add 1.52 g of 98% pure DMPA, adjust the system concentration to 25% using cyclohexanone as solvent, and control the isocyanate index R to 0.9. Start stirring, heat to 90℃, and react at this temperature for 7 h. Take a sample to check the NCO residue until it stabilizes, cool to room temperature to obtain PU-OH, and seal for later use.
[0116] Add 10.0 g of PU-OH to a four-necked flask and stir until evenly dispersed. Prepare 2 g of a 10% (w / w) solution of 2,3-epoxypropyltrimethylammonium chloride-chloroform and slowly add it dropwise to the PU-OH system. After the addition is complete, adjust the reaction temperature to 60℃ and react at this temperature for 6 h to obtain PU-OH-QAS. After cooling to room temperature, seal and store for later use.
[0117] 10 g of PU-OH-QAS was applied to an iron sheet and cured for 8 hours. Its hydrophilicity and anti-icing properties were then measured.
[0118] Comparative Example 1 Test-grade tinplate sheet, 100*60*0.3mm.
[0119] Comparative Example 2 A four-necked flask reaction system equipped with a stirrer, thermometer, and reflux condenser was constructed. After checking the seal, 40.0 g of PCL-2000 and 7.5 g of MDI-50 were added, and butyl acetate was added to adjust the system concentration to 50%. The stirrer was turned on (250 r / min), and the temperature was slowly increased to 90 °C. The reaction was carried out at a constant temperature for 7 h to obtain PrePU. The PrePU was then cooled to room temperature and sealed for later use. Using the same reaction apparatus, all of the PrePU was added to a four-necked flask, and cyclohexanone was added as a solvent to adjust the system concentration to 25%. 1.05 g of 98% pure DMPA was added as a chain extender, and the isocyanate index R was controlled to 1.3. Stirring was started, the temperature was raised to 90°C, and the reaction was maintained at this temperature for 7 hours. Samples were taken periodically during the reaction, and the residual amount of NCO groups in the system was determined by chemical titration until stable. The mixture was then cooled to room temperature to obtain PU-NCO, which was sealed for later use.
[0120] Apply 10 g of PU-NCO to the iron sheet.
[0121] The FT-IR spectra of PU-NCO and PU-NCO-QAS prepared in Example 4 are as follows: Figure 2 As shown, the FTIR spectra of the polyurethane sample before quaternization exhibit distinct carboxylic acid group characteristics: at 1700 cm⁻¹ -1 A clear absorption peak of the stretching vibration of the carboxylic acid carbonyl group (COOH) appeared nearby, along with a peak at 2500 cm⁻¹. -1 -3300cm -1 A broad and diffuse absorption band appeared within the range, corresponding to the stretching vibration of OH in the carboxylic acid. The broadened peak shape indicates strong intermolecular hydrogen bonding, which is perfectly consistent with the characteristics of the carboxylic acid group introduced into the DMPA side chain. After quaternization modification, the FTIR spectrum of the polyurethane sample changed significantly. First, the characteristic absorption associated with the carboxylic acid group was significantly weakened: at 1700 cm⁻¹... -1 The absorption peak intensity of the COOH carbonyl group at 2500 cm⁻¹ decreased significantly, while the intensity of the absorption peak at 2500 cm⁻¹ decreased significantly. -1 -3300cm -1 The broad absorption band of carboxylic acid OH in the range essentially disappears. Meanwhile, at 1550 cm⁻¹... -1 -1610cm -1 and 1390cm -1 -1450cm -1 The appearance of new characteristic absorption peaks or significantly enhanced peak intensities at these two locations can be attributed to carboxylate ions (COO₂) respectively. - Antisymmetric stretching vibration and symmetric stretching vibration.
[0122] The Fourier Transmission Infrared Spectrum (FT-IR) of the PU-OH-QAS prepared in Example 1 is shown below. Figure 3 As shown, compared to the PU-NCO-QAS sample, PU-OH-QAS at 3300 cm⁻¹... -1 A wide and diffuse absorption band appeared on both sides, which corresponds to the stretching vibration of the OH groups at the ends of the polyurethane. The reaction of the quaternary ammonium salt does not affect the OH groups at both ends of the polyurethane.
[0123] The nitrogen (N) content on the surface of the anti-icing coatings obtained in the examples and comparative examples was determined using the following method: Polyurethane anti-icing coating samples were selected, and their surface elemental composition and chemical state were analyzed using XPS. Before testing, the sample surface was cleaned to ensure it was smooth and free of impurities. Al Kα rays from a Thermo Kalpha instrument were used as the excitation source, with a test voltage of 1486.6 eV. Binding energy correction was based on C 1s (284.8 eV). The test results are shown in Table 1.
[0124] Table 1
[0125] As can be seen from Table 1, the N content on the surface of the anti-icing coatings of Examples 1 to 12 of the present invention is increased to 10% to 25%, which is significantly higher than that of Comparative Example 2. This shows that the quaternary ammonium salt was successfully grafted onto the surface of the anti-icing coating. The higher the N content, the higher the content of quaternary ammonium salt that migrates and distributes on the surface of the anti-icing coating, and the hydrophilicity of the anti-icing coating is significantly increased.
[0126] The contact angle between the anti-icing coatings obtained in the examples and comparative examples and water was determined. The test method is as follows: The surface contact angle was measured using an OCA20 contact angle meter (Data Physics, Germany), with deionized water as the test liquid and room temperature (25 ℃). Five different test points were selected for each sample, and a drop of deionized water (5 μL) was added. After the droplet stabilized (approximately 30 s), an image of the droplet was taken and the contact angle value was calculated. The average value of the five test points was taken as the final contact angle of the sample. The results are shown in Table 2.
[0127] The surface water contact angle of the anti-icing coating in Example 1 is as follows: Figure 4 As shown, the contact angle between the anti-icing coating surface of Example 1 and water is 40°.
[0128] The anti-icing coatings obtained in the examples and comparative examples were tested for freezing time in a -15℃ low-temperature test chamber. The test method was as follows: The anti-icing performance of the four polyurethane coatings was tested using a combination of a low-temperature constant temperature chamber and a weighing method. The test temperature was set at -10℃, and the test time was 1 hour. The coating samples were placed in a professional low-temperature test chamber (purchased from Hongyi Instrument Equipment Co., Ltd.). After the sample temperature stabilized at -10℃, an appropriate amount of deionized water (approximately 1 mL) was dripped onto the sample surface, and the freezing time was recorded. The test results are shown in Table 2.
[0129] Table 2
[0130] As can be seen from Table 2, the anti-icing coatings prepared in Examples 1-12 of the present invention have smaller surface water contact angles than those in the comparative examples. This indicates that the anti-icing coatings in Examples 1-12 have better hydrophilicity. The anti-icing coatings prepared in Examples 1-12 also have longer initial freezing time and freezing time after 20 cycles, which are significantly better than the anti-icing effects of comparative examples 1 and 2. Therefore, the anti-icing coatings prepared using the anti-icing coatings of the present invention have superior anti-icing performance, good hydrophilicity, good durability, and less degradation in anti-icing efficiency.
[0131] In summary, the anti-icing coating prepared by this invention has excellent hydrophilicity and its anti-icing efficiency is not easily reduced.
[0132] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a quaternary ammonium salt modified polyurethane anti-icing coating, characterized in that, Includes the following steps: S1. Polyol, polyisocyanate and first organic solvent are mixed and subjected to first heating reflux reaction in the absence of air to obtain isocyanate-terminated PrePU; S2. The isocyanate-terminated PrePU, chain extender and second organic solvent are mixed, and the isocyanate index R is controlled to 0.6 ~ 0.9 or 1.1 ~ 1.
5. Under the isolation of air, the second heating reflux reaction is carried out and cooled to obtain PU-OH or PU-NCO respectively. S3. Add the quaternary ammonium salt solution to the PU-OH or the PU-NCO, react, and obtain a solution containing PU-OH-QAS or a solution containing PU-NCO-QAS, wherein the quaternary ammonium salt solution includes 2,3-epoxypropyltrimethylammonium chloride and a third organic solvent. S4. Apply a solution containing PU-OH-QAS or a solution containing PU-NCO-QAS to the surface of the substrate and cure it to obtain a quaternary ammonium salt modified polyurethane anti-icing coating.
2. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to claim 1, characterized in that, The polyol includes one or more of polycaprolactone diol, polyether diol, and polycarbonate diol; and / or, The polyisocyanate is a diisocyanate, including one or more of diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate; The first organic solvent includes one or more of ethyl acetate, butyl acetate, and cyclohexanone; The isocyanate index R of the polyol and the polyisocyanate is 1.2 to 1.5; In the mixture of the polyol, the polyisocyanate, and the first organic solvent, the total mass percentage of the polyol and the polyisocyanate is 30% to 70%. The first heating reflux reaction was carried out under stirring at a speed of 200 r / min ~ 400 r / min; The temperature of the first heating reflux reaction is 80℃ ~ 100℃; The first heating reflux reaction takes 6 h to 8 h.
3. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to claim 1, characterized in that, The polyol includes polycaprolactone diol, wherein the number average molecular weight of the polycaprolactone diol is 500 to 10,000. The polyisocyanate includes diisocyanate, which includes one or more of diphenylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
4. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to claim 1, characterized in that, The chain extender includes 2,2-dimethylolpropionic acid; The second organic solvent includes one or more of cyclohexanone, ethyl acetate, and butyl acetate; In the mixture of isocyanate-terminated PrePU, chain extender, and second organic solvent, the combined mass percentage of the isocyanate-terminated PrePU and the chain extender is 15% to 30%.
5. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to claim 1, characterized in that, The second heating and reflux reaction is carried out under stirring at a speed of 200 r / min ~ 400 r / min; The temperature of the second heating reflux reaction is 80℃ ~ 100℃; The second heating reflux reaction takes 6 h to 8 h.
6. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to claim 1, characterized in that, In step S3, In the quaternary ammonium salt solution, the mass percentage of 2,3-epoxypropyltrimethylammonium chloride is 5% to 20%. The third organic solvent includes trichloromethane; The amount of 2,3-epoxypropyltrimethylammonium chloride is equal to the amount of the chain extender.
7. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to claim 1, characterized in that, In step S3, The quaternary ammonium salt solution is added at a rate of 0.5 mL / min to 2 mL / min. The reaction temperature is 40℃ ~ 60℃; The reaction time is 6 h to 8 h; The reaction was carried out under stirring.
8. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to claim 1, characterized in that, On the substrate, the areal density of PU-OH-QAS or PU-NCO-QAS is 0.01 g / cm³. 2 ~ 0.05 g / cm 2 .
9. The method for preparing the quaternary ammonium salt modified polyurethane anti-icing coating according to any one of claims 1 to 8, characterized in that, The substrate includes a metal sheet, which may be one or more of iron, steel, aluminum, and copper sheets.
10. A quaternary ammonium salt modified polyurethane anti-icing coating, characterized in that, The anti-icing coating is prepared using the method for preparing quaternary ammonium salt modified polyurethane anti-icing coating according to any one of claims 1 to 9.